Perlindungan Hukum Kesehatan Reproduksi Remaja dalam Perspektif Maqāṣid al-Sharī‘ah dan Prinsip Kepentingan Terbaik Anak - Zahrotun Nadhifah; Muhammad Dzikirullah H. Noho (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to analyze the implementation of reproductive health law in schools, the urgency of standardizing its regulation, as well as building a concept of legal protection that integrates national norms and Islamic Shari'ah principles. The research was conducted in three formal schools: SMPN 1 Jombang, SMPN 3 Peterongan (pesantren-based), and SMAN 2 Jombang, using empirical legal method with sociological juridical approach. The results show that despite efforts through education, UKS and screening, there are no uniform and binding technical legal standards. This leads to imbalances in implementation and weak comprehensive legal protection. From the perspective of maqāṣid al-sharī'ah and the principle of children's best interests, a legal system is needed that not only protects physical health, but also reason, morals, and religious values. Therefore, standardization of maqāṣid-based legal regulation and child protection is very important. Standardization that harmonizes maqāṣid values, the principle of children's best interests, and the theory of preventive and repressive legal protection, with the involvement of all elements of rule makers, implementers, and beneficiaries, is expected to guide regional policies to create a healthy, moral, and legally protected young generation in the context of a religious society such as Jombang Regency